Impact of Gross National Happiness (GNH) on the Adoption of Green Transportation in Bhutan - Haridev Singh, Elangbam; Phuntsho, Jigme (Prabandhan: Indian Journal of Management, 2015)
The GNH-led Kingdom of Bhutan has over 70% of its total area under forest cover and has made an ambitious declaration to ensure that greenhouse gas emission levels do not exceed the sequestration capacity of its forests at all times. However, in the face of rapid economic development which poses serious challenges to these conscious national efforts, the nature of Bhutanese transportation behavior, which (transportation) is a problem worldwide, has not been empirically studied. The purpose of this study was to determine whether GNH domain of ecological diversity and resilience, which includes, among others, the perceptions regarding environmental challenges, urban issues and responsibilities, had any effect on green transportation behavior of the Bhutanese students. Data collected from 300 college students were analyzed using appropriate multivariate logistic regression. As observed by many earlier studies, the present study did not find any significant relationship between selected GNH domains and green transportation.